ESPIRITUALIDADE E PEDAGOGIA DO DESEJO: UM DIÁLOGO ENTRE PAULO FREIRE E RENÉ GIRARD - Lopes, Leandro de Proença (2008)
The exploration and the manipulation of desire are some of the main brand of consumption culture. In the societies where predominate this culture, the consumption appears as a humanization criterion, and the meaning of life the ethical-mythical core, around in which society organize itself its the wealth accumulation seek to consume more. Some researches have been demonstrating the holy aspects of this culture, which became a real religion of the everyday life, with its devotions, spiritualities, myths, and rituals. At this same aspect, some studies have been demonstrating how this culture determines the pedagogic projects. Theses arent accidentals studies, because religion and education are essential elements in the origin and upkeep of any culture and human society. However it could also be transformation elements. Paulo Freire emphasize with interest in a Desire Pedagogy creation, and comprehend that the desire theme is extremely important in the improvement fight of social exclusion. But unfortunately he hadnt time to couch such pedagogy. The René Girard work reinforces the thesis that religion is an essential process for the human societies, considering the real function in the culture origin. According to Girard, religion is the humanity educationalist in the humanization and socialization process. And his most notable characteristic is exactly to educate the desire, because, due its mimetic nature, is constantly the violence generator. In the research of relations between Religion/ Theology and Education, recently has been accomplished the presupposed theologies and spiritual studies of the educational offers. Even thought that Paulo Freire and René Girard are at different areas, with different projects, there is lots of convergences aspects between them, some even complementary. The dialog between these two authors shows it very profitable in the theme of desire discussion in relation with the spirituality and education. This work is a try to search elements that promote the elaboration of a Desire Pedagogy starting with the contribution of the Religion Science.(AU)